Improving Attention Abilities in Children with ADHD Characteristics through the Multisensory VAKT Method - Rustiana, Rustiana; Pamungkas, Bayu (Journal of Innovation and Research in Primary Education, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) affects 5-7% of school-aged children globally, with affected children experiencing significant difficulties in maintaining focus, completing tasks, and adapting to educational environments. This study investigated the effectiveness of the Visual, Auditory, Kinesthetic, and Tactile (VAKT) method in improving attention abilities among early childhood children with ADHD characteristics. The research employed classroom action research design utilizing the Kemmis and McTaggart model across two implementation cycles at TK Negeri 1 Kec. Sangatta Selatan during the 2024/2025 academic year. Fifteen children from Group B2 participated, with particular focus on four children displaying ADHD characteristics including attention difficulties and disruptive behaviors. Data collection utilized structured behavioral observations assessing attention development across visual, auditory, kinesthetic, and tactile modalities using a four-point developmental scale. The intervention integrated multisensory activities including picture guessing games, animal sound imitation, obstacle courses, mystery box exploration, and finger painting activities designed to simultaneously engage all sensory processing systems. Results demonstrated substantial progressive improvements, with overall attention development scores increasing from 49.99% at baseline to 83.21% following Cycle II implementation, representing a 33.22 percentage point improvement. Among children with ADHD characteristics, three of four participants advanced to "Developing as Expected" category, showing marked improvements in sustained attention, reduced disruptive behaviors, and enhanced task completion. The VAKT method effectively addressed fundamental attention deficits by providing multiple simultaneous processing pathways that compensated for compromised executive function systems. These findings provide empirical evidence that theoretically-grounded multisensory interventions can produce meaningful improvements in attention capabilities, offering practical solutions for inclusive early childhood education settings serving children with diverse learning needs and neurodevelopmental differences.